The Analysis on Combination Indemnity Claims Upon the Cancellation Act of Unilateral Agreement - Sarfia Nengsih; Eliza Maureen Kristianto; Riski Pebru Ariyanti (Fakultas Hukum Universitas Hang Tuah, 2019)
In reality, there is a possibility that a party unilaterally canceled (before the agreement is implemented). This course can be detrimental to others, on the basis of which the aggrieved party should be able to claim compensation. To make demands, it needs the right legal basis. Whether it isa default or illegal act. There are major differences in claims on the basis of default and claims based on illegal acts. Because there is a difference between claims for compensation in default and illegal acts, a study of agreement cancellation is needed unilaterally. Merging claims against law and default agreements is possible because it does not conflict with the law and in accordance with the jurisprudence and the opinion of Supomo that the claim merger requires a close relationship (innerlickesamenhangen). As a result of the law being granted, the merging claims of unlawful conduct and default in the aforementioned decision, the judge sentenced the Defendant for the act against the law and Default to the Defendant to pay material compensation which is obviously suffered and the Immaterial loss in the form sum of money payment.